Transformasi Lignoselulosa Ampas Kopi melalui Perlakuan Beku–Cair untuk Meningkatkan Efisiensi Biokonversi - Margareta Cahyanti; Diki Anggaran; Yefta A Steefian; Vincentia N. P. Kristanti (Akta Kimia Indonesia, 2025)
Spent coffee grounds are an abundant waste material that also holds great potential as a renewable biomass resource. In this study, a simple freeze–thaw treatment was applied repeatedly to investigate its effect on the extractive content and fiber composition of spent coffee grounds. Furthermore, the reducing sugar content obtained after acid hydrolysis was measured to evaluate its potential for microbial conversion. The results showed that the extractive content reached its lowest value after five freeze–thaw cycles, at 10.59%. Hemicellulose content increased with the number of treatment cycles but decreased again at the fifth cycle. Cellulose content exhibited a fluctuating trend across treatments, whereas lignin content remained relatively stable after one and three cycles and increased after five cycles. The reducing sugar concentration increased by more than 16%, from 38.21 g/kg in the untreated sample to 44.70 g/kg after five cycles of treatment. This increase indicates cell wall disruption and the removal of extractives, which enhanced cellulose accessibility during hydrolysis. Overall, the findings demonstrate that the freeze–thaw treatment is an effective, environmentally friendly, and economical approach to enhance the saccharification potential of coffee grounds, offering a promising route for biomass valorization and sustainable bioenergy production.